PENGEMBANGAN FLASHCARD AUGMENTED REALITY (AR) BERBANTUAN ASSAMBLER EDU PADA PENGENALAN ALAT MUSIK RITMIS DAN MELODIS DI SDN 104202 BANDAR SETIA - Ananda Tampubolon; Try Wahyu Purnomo; Putra Afriadi; Sri Mustika Aulia; Natalia Silalahi (STKIP Subang, 2026)
This study was motivated by limited use innovative learning media and technology integration in music education at the elementary school level, which caused students to experience difficulties in understanding rhythmic and melodic musical instruments. The study aimed to develop an Augmented Reality (AR)-based Flashcard learning media assited by Assambler Edu that is valid, practical, and effective. This research employed the Research and Development (R&D) method using the ADDIE model, which consist the five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were All Fifth-grade students of SDN 104202 Bandar Setia. Data were collected through interviews, questionnaires, and learning achievement tests. The results showed that the developed media achieved validity scores of 84% from material expert and 90%from the media expert, both categorized as highly valid. The practicality test yielded a score of 95,7%, indicating a highly practical category. The effectiveness test demonstrated an improvement in students average score from 46.65 on the pre-test to 84.56 on the post-test, with an N-Gain score of 0.72, categorized as high. Therefore, the Augmented Reality (AR)-based Flashcard assited by Assambler Edu was found to be valid, practical, and effective for teaching rhythmic and melodic musical instruments in elementary school